KONDISI DAN UPAYA PELESTARIAN HUTAN MANGROVE YANG BERBASIS PENDEKATAN MASYARAKAT DI KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG SUMATERA UTARA - Dizza Ayu Putri; Yunasfi Djayus; Rita Rosmala Dewi (AQUACOASTMARINE, 2018)
Ecosystem of mangroves forest in the District of Percut Sei Tuan has a number of conversion that effected by aquaculture activities namely shrimp farming, then plantation activities such as palm oil plantation. Furthermore, the most utilization of mangrove that is done by society such as wood fuel and charcoal production. It causes permanent mangrove destruction and reduction in mangrove area which is lead to decrease in ecological function and benefit of mangrove ecosystem. The purpose of this study is to determine the condition and the dominant species of mangrove, hence how the coastal society effort in dealing with mangrove forest destruction. This research was conducted in May - June 2017. The research was conducted by survey method and purposive sampling. The result showed that mangrove condition in Percut Sei Tuan Subdistrict of Deli Serdang Regency was in rare state. And also found the most widely Plants of Nipah up to 2.000 Tree/ha. Condition of water parameters (temperature, salinity, pH) fulfill the quality standard of Decree of LH No. 51 of 2004. The value of mangrove landform changes as much as 64% which is used as palm oil plantation and 36% used as pond area and the utilization of mangrove as fishing (fish, shrimp, crab, et all) and charcoal fuel which resulted in decreasing of mangrove land in Percut Sei Tuan Subdistrict of Deli Serdang Regency of North Sumatera.Keywords : Mangrove, Transformation area, Sub-district Percut Sei Tuan, Deli Serdang district